2023
DOI: 10.1155/2023/1403704
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Azolla, Azolla pinnata as a Complementary Feed for Oreochromis niloticus: Growth, Digestive Enzymes, Intestinal Morphology, Physiological Responses, and Flesh Quality

Abstract: Azolla is a potential fish feed ingredient due to its high nutritional value, abundant production, and low price. This study is aimed at evaluating the use of fresh green azolla (FGA) as a replacement ratio of the daily feed intake on the growth, digestive enzymes, hematobiochemical indices, antioxidant response, intestinal histology, body composition, and flesh quality of monosex Nile tilapia, Oreochromis niloticus (with an average initial weight of 108.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…The researchers also suggested that substituting dietary components with up to 20% Azolla could be a viable feeding strategy for monosex Nile tilapia. This approach has the potential to enhance fish growth, quality, profitability, and sustainability within the tilapia production industry (Refaey et al, 2023).…”
Section: Fig 1 Survival Rate (%) Of Different Treatments At the End O...mentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers also suggested that substituting dietary components with up to 20% Azolla could be a viable feeding strategy for monosex Nile tilapia. This approach has the potential to enhance fish growth, quality, profitability, and sustainability within the tilapia production industry (Refaey et al, 2023).…”
Section: Fig 1 Survival Rate (%) Of Different Treatments At the End O...mentioning
confidence: 99%
“…This leads to an increase in the overall productivity of ponds. Additionally, the rapid decomposition rates of Azolla make it an excellent substrate for microbial processing, such as composting, or for enhancing the detrital food chain before it is applied to ponds [7,8]. Rohu is a preferred Indian major carp species for cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of Azolla in the right proportion can enhance fish growth and development, leading to increased productivity. High levels of Azolla inclusion can potentially weaken digestion and reduce feed consumption by impacting the activity of digestive enzymes [25,76]. Several studies have been conducted to determine the digestibility of Azolla, and the results have shown promising outcomes.…”
Section: The Impact Of Using the Azolla Plant As A Fish Diet On Growt...mentioning
confidence: 99%
“…Fish culture in artificial environments may affect physiological responses and behavior of farmed fish [1][2][3][4]. The tank color is an important parameter for fish welfare and it must be considered for enhancing performance of cultured fish [5,6].…”
Section: Introductionmentioning
confidence: 99%